Labour shortage in Russia: education and productivity in the context of demographic decline ("Journal "U". Economy. Management. Finance.", 2026)
The article analyses a dual-track strategy for addressing labour shortages in Russia: the development of secondary vocational education and the enhancement of labour productivity. Challenges, instruments, risks, and recommendations for improving state policy under conditions of demographic decline are examined.
Keywords: labour shortage; secondary vocational education; labour productivity; state strategy